Răspuns :
Răspuns:
- x = 13
Explicație pas cu pas:
(x + 2) / 9 = 1 intreg 2/3
(x + 2) / 9 = (1×3+2) / 3
(x + 2) / 9 = 5 / 3
3 × (x + 2) = 9 × 5
3x + 6 = 45
3x = 45 - 6
3x = 39
x = 39 : 3
x = 13
Răspuns: [tex]\red{ \boxed{\bf x = 13}}[/tex]
Explicație pas cu pas:
Bună !
[tex]\bf \dfrac{x+2}{9} =1\dfrac{2}{3}\implies \dfrac{x+2}{9} =\dfrac{1\cdot3+2}{3}\implies[/tex]
[tex]\bf \dfrac{x+2}{9} =\dfrac{5}{3}~\xrightarrow[pe~diagonala~]{~inmultim~} 3\cdot (x+2)= 9\cdot 5 \implies 3x+6 = 45[/tex]
[tex]\bf 3x = 45-6\implies 3x = 39~~\bigg|:3\implies \red{ \boxed{\bf x = 13}}[/tex]
P.S.: Dacă ești pe telefon te rog să glisezi spre stânga pentru a vedea întreaga rezolvare.
Baftă multă !